Vine Water Deficit Impacts Aging Bouquet in Fine Red Bordeaux Wine - Picard, Magali; van Leeuwen, Cornelis; Guyon, François; Gaillard, Laetitia; de Revel, Gilles; Marchand, Stéphanie (Frontiers in Chemistry, 2017)
The aim of this study was to investigate the influence of vine water status on bouquet typicality, revealed after aging, and the perception of three aromatic notes (mint, truffle, and undergrowth) in bottled fine red Bordeaux wines. To address the issue of the role of vine water deficit in the overall quality of fine aged wines, a large set of wines from four Bordeaux appellations were subjected to sensory analysis. As vine water status can be characterized by carbon isotope discrimination (δ13C), this ratio was quantified for each wine studied. Statistical analyses combining δ13C and sensory data highlighted that δ13C values discriminated effectively between the most- and least-typical wines. In addition, Principal Component Analysis revealed correlations between δ13C values and truffle, undergrowth, and mint aromatic notes, three characteristics of the red Bordeaux wine aging bouquet. These correlations were confirmed to be significant using a Spearman statistical test. This study highlighted for the first time that vine water deficit positively relates to the perception of aging bouquet typicality, as well as the expression of its key aromatic nuances.